Pengaruh Testimoni dan Diskon terhadap Keputusan Pembelian Sepatu New Balance: Peran Gender sebagai Variabel Moderasi pada Generasi Z - Rida Haris, Kadarisman; Fadjar, Adfiyani; Muzakir; Ega Nugraha, Mohammad (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of testimonials and discounts on purchasing decisions for New Balance shoes in generation Z. The sample used in this study was 96 people with purposive sampling technique. The data were collected using a questionnaire and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) with the help of Smart PLS 4.0 software. The results showed that testimonials and discounts partially had a positive and significant effect on purchasing decisions for New Balance shoes. In addition, testimonials and discounts also have a simultaneous positive and significant effect on purchasing decisions. These findings indicate that factors such as consumer reviews and discount offers have an important role in influencing purchasing decisions in generation Z, which can be a strategic consideration for companies in marketing New Balance shoe products to this market segment.